2022
DOI: 10.1109/tgrs.2021.3062492
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing of Precipitation Using Reflected GNSS Signals: Response Analysis of Polarimetric Observations

Abstract: For the first time, rain effects on the polarimetric observations of the Global Navigation Satellite System Reflectometry (GNSS-R) are investigated. The physical feasibility of tracking the modifications in the surface roughness by rain splash and the surface salinity by the accumulation of freshwater is theoretically discussed. An empirical analysis is carried out using measurements of a coastal GNSS-R station with two side-looking antennas in right and left-handed circular polarization (RHCP and LHCP). Disce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…and as the wind speed increases, the mss increments are marginal with respect to the mss in rain-free conditions, and therefore the change in the DDM peak is negligible. These large variations of the DDM peak are in agreement with the experimental results presented in [25] and [26].…”
Section: G Impact Of Rainsupporting
confidence: 92%
“…and as the wind speed increases, the mss increments are marginal with respect to the mss in rain-free conditions, and therefore the change in the DDM peak is negligible. These large variations of the DDM peak are in agreement with the experimental results presented in [25] and [26].…”
Section: G Impact Of Rainsupporting
confidence: 92%
“…Minfeng Song, Xiufeng He, Dongzhen Jia, Ruya Xiao, Xiaolei Wang, Zhetao Zhang are with the School of Earth Sciences and Engineering, Hohai gradually developed during recent decades since the first usage as a new remote sensing concept was proposed in [1] [2]. Numerous studies based on the spaceborne measurements demonstrated the potential of GNSS-R to sense the Earth's surface [3], including sea surface height [4] [5] [6], wind speed [7] [8], soil moisture [9][10], sea ice [11] [12], and potentially precipitation over calm oceans [13] [14]. Compared to spaceborne scenarios, the ground-based GNSS interferometry reflectometry (GNSS-IR) technique based on interference data represented by SNR records is an even lower cost and higher temporal and spatial resolution Earth monitoring approach.…”
mentioning
confidence: 99%
“…In addition, rainfall, as a common natural phenomenon at the sea surface, not only desalinates the salinity of seawater, but also causes changes in the roughness of the sea surface [41]. Although CYGNSS observables can provide some response to rainfall-induced roughness changes, this response is limited.…”
Section: Discussionmentioning
confidence: 99%